Strategic Leadership of The Principal in Improving Educational Quality at Mis Nidaul Insan Pantai Labu - Muhammad Iqbal (Sufiya Journal of Islamic Studies, 2023)
This research aims to explore the strategies carried out by madrasah heads in improving the quality of education. Using a descriptive qualitative approach, data was collected through in-depth interviews with key informants of teachers, principals and guardians. The results of the study showed that the head of the madrasah implemented a routine supervision strategy, evaluative meetings, and systematic pedagogical coaching. This strategy is supported by the provision of symbolic incentives and the formation of a work culture that is psychosocially conducive. However, the resistance of some teachers to change is the main challenge in the optimal implementation of the strategy. These findings indicate that top-down leadership models need to be supported by the internalization of teachers' professional awareness as well as stronger institutional support. This research emphasizes that improving the quality of education in village madrassas requires transformative leadership that is able to integrate strategic planning, collective participation, and continuous coaching in one place.